2001
DOI: 10.1136/bmj.322.7290.819
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal cohort study of childhood IQ and survival up to age 76

Abstract: Objectives To test the association between childhood IQ and mortality over the normal human lifespan. Design Longitudinal cohort study. Setting Aberdeen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
359
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(375 citation statements)
references
References 20 publications
11
359
1
4
Order By: Relevance
“…Several studies over the past two decades allude to this, as they have reported strong associations between a broader set of cognitive abilities and the aforementioned health outcomes associated with literacy skills. [13][14][15][16][17] In general, poorer cognitive performance has been linked to less health knowledge, poorer medication adherence, worse physical and mental health, and greater mortality risk. [18][19][20][21][22] A significant relationship is already known to exist between literacy and cognitive skills.…”
Section: Objectivementioning
confidence: 99%
“…Several studies over the past two decades allude to this, as they have reported strong associations between a broader set of cognitive abilities and the aforementioned health outcomes associated with literacy skills. [13][14][15][16][17] In general, poorer cognitive performance has been linked to less health knowledge, poorer medication adherence, worse physical and mental health, and greater mortality risk. [18][19][20][21][22] A significant relationship is already known to exist between literacy and cognitive skills.…”
Section: Objectivementioning
confidence: 99%
“…These include not only mortality 18 and disability 16 , but also occupational exposures 32 . Moreover, mental ability at age 11 is itself related to events earlier in life including those before birth 15 .…”
Section: Future Uses Of the Datamentioning
confidence: 99%
“…Identifying the period when IQ-associated health inequalities arise is important not only for the timing of possible interventions, but also allows inferences to be drawn about which mechanisms are involved. Previously, we hypothesised four pathways along which childhood IQ might affect survival: 1) as a record of bodily insults in early childhood, 2) as an indicator of system integrity, 3) as a predictor of health behaviours, and 4) as a predictor of entry into safer environments 18 . The first pathway implies that individual differences in health arise early in life and the second favours an increase with age as degenerative processes become more important.…”
Section: Future Uses Of the Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Relations between cognitive functioning and longevity have been shown to span multiple decades of the lifespan and to persist even after adjusting for socio-economic advantage, sensorimotor capabilities, self-reported health status, and a host of medical conditions (Anstey, Luszcz, Giles, & Andrews, 2001; Bosworth, Schaie, & Willis, 1999;Fried et al, 1998;Small & Bäckman, 1997;Whalley & Deary, 2001). In two large sample studies, the predictive strength of cognitive performance in relation to mortality risk was found to approach that of smoking, eclipsing the influence of variables such as body…”
Section: Introductionmentioning
confidence: 99%